2022
DOI: 10.1001/jamaoncol.2022.4079
|View full text |Cite
|
Sign up to set email alerts
|

Short-term Outcomes of Laparoscopy-Assisted vs Open Surgery for Patients With Low Rectal Cancer

Abstract: IMPORTANCE The efficacy of laparoscopic vs open surgery for patients with low rectal cancer has not been established. OBJECTIVE To compare the short-term efficacy of laparoscopic surgery vs open surgery for treatment of low rectal cancer. DESIGN, SETTING, AND PARTICIPANTS This multicenter, noninferiority randomized clinical trial was conducted in 22 tertiary hospitals across China. Patients scheduled for curative-intent resection of low rectal cancer were randomized at a 2:1 ratio to undergo laparoscopic or op… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

2
33
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 50 publications
(36 citation statements)
references
References 36 publications
2
33
1
Order By: Relevance
“…
COMMENT & RESPONSEIn Reply We appreciate the comments by Yuan et al regarding our recent Original Investigation. 1 During the surgical operation, we strictly followed the study design of at least 10 cm for proximal resection margin (PRM). The fact that one-fourth of patients in the laparoscopic group had a PRM of 9 cm or less most likely reflects the contraction of resected specimen from the time of resection to the time of measurement (typically at the end of surgery).
…”
supporting
confidence: 80%
“…
COMMENT & RESPONSEIn Reply We appreciate the comments by Yuan et al regarding our recent Original Investigation. 1 During the surgical operation, we strictly followed the study design of at least 10 cm for proximal resection margin (PRM). The fact that one-fourth of patients in the laparoscopic group had a PRM of 9 cm or less most likely reflects the contraction of resected specimen from the time of resection to the time of measurement (typically at the end of surgery).
…”
supporting
confidence: 80%
“…First, the authors reported a significantly shorter median length of proximal resection margin (PRM) in the laparoscopic group than the open group (124 vs 130 mm; P = .02). Additionally, the length of PRM of more than one-quarter of surgical specimens was 9 cm or less in the laparoscopic group, which is not consistent with the study design.…”
mentioning
confidence: 99%
“…Finally, as the authors mentioned, diverting ostomy was performed in patients with high-risk anastomosis. It is reported that fecal diversion does most benefit to patients with a low rectal anastomosis, male sex, or neoadjuvant radiotherapy .…”
mentioning
confidence: 99%
“…However, the time to first defecation of more than half of patients in the EA group and more than three-quarters of patients in the SA group was longer than 3 days, which was inferior to the results of a recently published study from China. 2 The detailed Enhanced Recovery After Surgery (ERAS) protocol and the actual patient adherence in this trial should have been reported by the authors to help evaluate the efficacy of EA objectively in the setting of ERAS. Besides, the occurrence rate of POI in this trial was significantly higher than in several randomized clinical trials.…”
mentioning
confidence: 99%
“…Besides, the occurrence rate of POI in this trial was significantly higher than in several randomized clinical trials. [2][3][4] It is critical for future studies to check and determine the definition and diagnostic criteria of POI.…”
mentioning
confidence: 99%